What is the definition of acute episodic and chronic pain in critically ill neonates and infants? A global, four-stage consensus and validation study. Issue 3 (9th March 2022) - Ilhan, Emre; Pacey, Verity; Brown, Laura; Spence, Kaye; van Ganzewinkel, Christ-jan; Pillai Riddell, Rebecca; Campbell-Yeo, Marsha; Stevens, Bonnie J; Eriksson, Mats; Shah, Vibhuti; Anand, Kanwaljeet J S; Bellieni, Carlo; et al.
Abstract : Objectives: To define and validate types of pain in critically ill neonates and infants by researchers and clinicians working in the neonatal intensive care unit (NICU) and high dependency unit (HDU). Design: A qualitative descriptive mixed-methods design. Procedure/s: Each stage of the study was built on and confirmed the previous stages. Stage 1 was an expert panel to develop definitions; stage 2 was a different expert panel made up of neonatal clinicians to propose clinical characteristics associated with the definitions from stage 1; stage 3 was a focus group of neonatal clinicians to provide clinical case scenarios associated with each definition and clinical characteristics; and stage 4 was a survey administered to neonatal clinicians internationally to test the validity of the definitions using the clinical case scenarios. Results: In stage 1, the panel (n=10) developed consensus definitions for acute episodic pain and chronic pain in neonates and infants. In stage 2, a panel (n=8) established clinical characteristics that may be associated with each definition. In stage 3, a focus group (n=11) created clinical case scenarios of neonates and infants with acute episodic pain, chronic pain and no pain using the definitions and clinical characteristics. In stage 4, the survey (n=182) revealed that the definitions allowed an excellent level of discrimination between case scenarios that described neonates and infants with acute episodic pain and chronic pain (area under the receiver operating characteristic=0.87 and 0.89, respectively). Conclusions: This four-stage study enabled the development of consensus-based and clinically valid definitions of acute episodic pain and chronic pain. There is a need to define and validate other pain types to inform a taxonomy of pain experienced by neonates and infants in the NICU and HDU.